Defining polypharmacy: in search of a more comprehensive determination method applied in a tertiary psychiatric hospital. (March 2021) - Govaerts, Jeroen; Boeyckens, Julie; Lammens, Astrid; Gilis, Annelies; Bouckaert, Filip; De Hert, Marc; De Lepeleire, Jan; Stubbs, Brendon; Desplenter, Franciska
Aims: This cross-sectional pharmacoepidemiologic study examined the prevalence of polypharmacy and psychotropic polypharmacy among inpatients in a tertiary psychiatric hospital in Belgium. Methods: Current prescriptions of all inpatients suffering from mental disorders were extracted from the hospital Computerized Physician Order Entry. Two methods were used to examine definitive polypharmacy (defined as the concomitant use of at least five medicines): number of medicines per active component and per prescription. Psychotropic polypharmacy was defined as the concomitant use of at least two psychotropic medicines, based on the first counting, i.e., per active component. Results: In 292 included patients, the prevalence of definitive polypharmacy was 65.8%, with a mean number of 6.8 ± 4.2 medicines per patient. The most prevalent medicines were related to the central nervous system (55.7%), followed by medicines related to the gastro-intestinal (17.6%) and cardiovascular (9.4%) systems. A prevalence of psychotropic polypharmacy of 78.1% was observed, with a mean of 3.0 ± 1.7 psychotropic medicines per patient. Psychotropic polypharmacy was classified in same-class (71.5%), multi-class (82.5%), augmentation (20.6%), and adjuvant (35.5%) polypharmacy. Conclusion: These findings are consistent with previous reports of highly prevalent polypharmacy in patients with mental disorders. Although, in some cases, polypharmacy can be an important part of good clinical practice, the high prevalence of both polypharmacy and psychotropic polypharmacy emphasizes that attention must be paid to the potentially associated risks. Consensus on the definition and method of determination of polypharmacy is needed to support further research.